2021
DOI: 10.1007/s00167-021-06728-z
|View full text |Cite
|
Sign up to set email alerts
|

Good clinical outcomes after patellar cartilage repair with no evidence for inferior results in complex cases with the need for additional patellofemoral realignment procedures: a systematic review

Abstract: Purpose Focal, patellar cartilage defects are a challenging problem as most cases have an underlying multifactorial pathogenesis. This systematic review of current literature analysed clinical results after regenerative cartilage repair of the patella with a special focus on the assessment and treatment of existing patellofemoral malalignment. Methods A systematic review was conducted to identify articles reporting clinical results after cartilage regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Second, as consecutive patients were included and inclusion criteria were not limited to isolated cartilage defects, the heterogeneity of the study population might pose a limitation. However, a recent systematic review demonstrated good clinical outcomes after cartilage repair at the patellofemoral joint even in complex cases [ 5 ]. Third, the majority of the cartilage defects were located at the patella or femoral condyle and only a few at the trochlea or tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, as consecutive patients were included and inclusion criteria were not limited to isolated cartilage defects, the heterogeneity of the study population might pose a limitation. However, a recent systematic review demonstrated good clinical outcomes after cartilage repair at the patellofemoral joint even in complex cases [ 5 ]. Third, the majority of the cartilage defects were located at the patella or femoral condyle and only a few at the trochlea or tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondral autograft transfer system (OATS), autologous chondrocyte implantation (ACI), matrix-assisted chondrocyte implantation (MACI) or several cartilage repair techniques using scafolds (natural or synthetic) are contemporarily the most commonly therapies for medium to large defects [7,22]. ACI and MACI are purported to generate hyaline or hyaline-like cartilage, with low associated reoperation rates and favourable clinical outcomes even in complex cases [5,7,18,29,49]. However, the two-step approach of ACI and MACI, which requires laboratory cell cultivation, results in a high inancial and clinical burden.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent literature has also demonstrated that analysis and, if applicable, therapy of possible co‐factors are crucial for good postoperative results. Accordingly, the importance of the coronal leg axis for the treatment of defects at the femoral condyles and the importance of patellofemoral alignment for the patellofemoral location have been emphasized [3, 5, 11, 32].…”
Section: Introductionmentioning
confidence: 99%
“… 5 Satisfactory results have been published after autologous chondrocyte implantation in cases of large defects. 6 , 7 For smaller defects with substantial bone loss, autologous osteochondral transplantation may be a reasonable treatment option. 5 , 6 …”
mentioning
confidence: 99%